Who Wants to Be a Nervous System Infection Genius: A Case-Based Microbiology Game on Nervous System Infections - Melphine Harriott (Association of American Medical Colleges, 2013)
Abstract This interactive team-based game was developed to review nervous system pathogens during a neuroscience course in our organ system-based curriculum. It is a team activity that is intended for first- or second-year medical students. The game consists of nine short case studies with two or three associated questions per case, which teams answer with a team audience response system remote. Each question is assigned a point value, so that the team with the highest points wins the game. In between each case, there is a built-in instructor-facilitated discussion time, which ensures student questions or unclear concepts are addressed in a timely manner. This session provides students an opportunity to review microbiology in the context of the nervous system. The game atmosphere stimulates healthy competition between teams. However, because this session is non-graded, students are more relaxed and more willing to participate both in the small-group and larger classroom discussions. Finally, the use of the audience response system allows the instructor to receive real-time feedback on students answer choices and immediately clarify unclear concepts.